If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 5 + 2(7c + 1) Reorder the terms: 7 = 5 + 2(1 + 7c) 7 = 5 + (1 * 2 + 7c * 2) 7 = 5 + (2 + 14c) Combine like terms: 5 + 2 = 7 7 = 7 + 14c Add '-7' to each side of the equation. 7 + -7 = 7 + -7 + 14c Combine like terms: 7 + -7 = 0 0 = 7 + -7 + 14c Combine like terms: 7 + -7 = 0 0 = 0 + 14c 0 = 14c Solving 0 = 14c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-14c' to each side of the equation. 0 + -14c = 14c + -14c Remove the zero: -14c = 14c + -14c Combine like terms: 14c + -14c = 0 -14c = 0 Divide each side by '-14'. c = 0 Simplifying c = 0
| 4-12=5s+51 | | (50-2x)*x=200 | | (7+2)xX+1= | | 5x+61=73+2x | | -g=1.5g-3 | | m(x)=(3x-1)(3-x)+4x^3+19 | | y=(20+x)(3000-100x) | | -0.75x=0.86 | | (3-9x)= | | 3=4-3(5c-1) | | 20+10m=200 | | 5b-14-3b=30 | | 15-5x=26 | | 6x+7x=16 | | 2x-2=4(x-1) | | 9a+3a+12=36 | | -5+7(k+6)=93 | | 6(-p)=54 | | x^2+4x+2=5x+7 | | -2m+19= | | 35+80h=915 | | 73-17=46+7 | | -9(8-9m+n)= | | 3x^3-4x^3= | | -4(7v-7)+5v=-87 | | 2x^2-20x+100=108 | | 5x+3y+2z=4 | | 2(10)+3y=24 | | 2(x+3y)+4(x+5y)-3x= | | (42+2x)=(3x+4) | | 2(10.4)+3y=24 | | -2(y-3)=-6y-12+2y |